PENGARUH STATUS SOSIAL EKONOMI ORANG TUA TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPS KELAS VII DI SMP N 2 KUANTAN MUDIK, KAB. KUANTAN SINGINGI TAHU AJARAN 2012-2013 - Raja Andina; Bedriati Ibrahim; Marwoto Saiman (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract: In the process of education, parental background differences have a very important role and influence of such a magnitude to send their children. Socio-economic conditions should be taken to ensure that educational success can be achieved to the fullest. Smp n 2 Kuantan Mudik is one who has the role of formal education to improve the quality of education. Students who attend also come from family backgrounds var . There is work as farmers, laborers, etc. rubber cutter .Based on field observations, encountered students who have parents with high incomes obtain a low learning outcomes, and vice versa .This type of research used is descriptive research with samples from 36 people. The data collected was obtained from 33 question items in the questionnaires that spread to parents of students, and 10 items from the interview question class VII. While the learning outcomes of students in the can from social studies grades 2nd semester school year 2012-2013 with an average yield of between 75-90 students with KKM 75.Recapitulation of the questionnaire can be known about the socioeconomic status of the parents of students of class VII in SMP N 2 Kuantan Mudik shows the results of " moderate / medium " that is 59.3% because the value is in the range 50% -75% . Means it can be seen that the socioeconomic status of the parents " influence " on student learning outcomes in social studies class VII in SMP N 2 Kuantan Mudik, Kab. Kuantan Singingi 2012-2013 school year .Keywords : parental socioeconomic status, learning outcomes